Aged garlic extract suppresses the increase of plasma glycated albumin level and enhances the AMP‐activated protein kinase in adipose tissue in TSOD mice. Issue 5 (21st February 2017) - Miki, Satomi; Inokuma, Ken‐ichi; Takashima, Miyuki; Nishida, Mitsuho; Sasaki, Yoko; Ushijima, Mitsuyasu; Suzuki, Jun‐ichiro; Morihara, Naoaki
Abstract : Aged garlic extract reduced the plasma level of glycated albumin by activating the AMPK and suppressing the expression of FAS and MCP1 in adipose tissue. Abstract : Scope: In this study, we investigated the effect of aged garlic extract (AGE) on the high level of blood glucose in Tsumura Suzuki Obese‐Diabetes (TSOD) mice. Methods and results: TSOD mice were fed standard diet with or without 2% AGE for 19 weeks. AGE treatment lowered the blood glucose level and significantly reduced the plasma level of glycated albumin in TSOD mice as compared with those without AGE treatment. In addition, AGE treatment increased the level of phosphorylated AMP‐activated protein kinase (AMPK) in the adipose tissue, liver and muscle that played an important role in the maintenance of insulin sensitivity. Moreover, AGE treatment also suppressed the mRNA expression of fatty acid synthase, a known factor regulated by AMPK, and monocyte chemoattractant protein 1, one of the representative inflammatory chemokines, in the adipose tissue but not in the liver. Conclusion: AGE treatment suppresses the increase of plasma glycated albumin level in TSOD mice and this effect is accompanied by the activation of AMPK in adipose tissue, and suggests that AGE may play a potential role in the prevention and treatment of type 2 diabetes.